THE INFLUENCE OF BALANCED SCORECARD AND VALUE CHAIN ON FINANCIAL PERFORMANCE AT X UNIVERSITY SURABAYA - Lim, Angelica; Marlina, Maria Asumpta Evi (Program Studi Diploma III Akuntansi Fakultas Ekonomi dan Bisnis Universitas Mataram, 2026)
This study examines the impact of the Balanced Scorecard (BSC) and Value Chain on financial performance in higher education, utilizing X University Surabaya as a case study. Unlike prior studies that analyzed these frameworks separately, this research integrates both to provide a comprehensive model of strategic and financial alignment. Using a quantitative approach with Structural Equation Modelling–Partial Least Squares (SEM-PLS), data were collected from 101 academic and administrative staff members between February and April 2025. The findings indicate that internal business processes and learning and growth perspectives have a significant impact on the value chain, whereas the financial Perspective is not significant. The customer perspective has a moderate positive effect. The value chain mediates the relationship between BSC perspectives and financial performance. These results suggest that enhancing internal efficiency, innovation, and human resource development is crucial for financial sustainability in universities.